Bridging the Gap: Incorporating African Indigenous Knowledge Systems into Modern Education - Babalola, JOEL B.; ADEMOLA I, Atanda (International Journal of Educational Management, 2025)
Systems (AIKS) into the educational curriculum, a topic of increasing relevance in the contemporary educational landscape. AIKS, deeply rooted in African cultures and traditions, have been cultivated and passed down through generations for thousands of years. These systems are based on personal experience and culture, emphasizing interpersonal relationships, and are informed by and relate to all domains of life and the environment. Despite the immense value and unique perspective, the incorporation of AIKS into formal education presents several challenges. This paper systematically discusses these challenges, which include time constraints during lessons, lack of clear support, limited content and materials, inadequate AIKS qualified staff, and lack of technical provision and professional support. Drawing from a range of scholarly sources, the paper proposes effective strategies for overcoming these challenges. These strategies emphasize the need for a strong institutional support system, the importance of considering indigenous or local knowledge when developing policies and practices, and the use of AIKS to analyze African Inclusive Education relevant to the African context. The paper concludes with a call for further research and understanding of AIKS and how they can be effectively incorporated into the school curricula, thereby not only enriching the learning experience of students but also helping to preserve and promote these valuable Indigenous knowledge systems for future generations